In-Depth Molecular Profiling Specifies Human Retinal Microglia Identity - Wolf, Julian; Boneva, Stefaniya; Rosmus, Dennis-Dominik; Agostini, Hansjürgen; Schlunck, Günther; Wieghofer, Peter; Schlecht, Anja; Lange, Clemens (Frontiers in Immunology, 2022)
Microglia are the tissue-resident macrophages of the retina and brain, being critically involved in organ development, tissue homeostasis, and response to cellular damage. Until now, little is known about the molecular signature of human retinal microglia and how it differs from the one of peripheral monocytes and brain microglia. In addition, it is not yet clear to what extent murine retinal microglia resemble those of humans, which represents an important prerequisite for translational research. The present study applies fluorescence-activated cell sorting to isolate human retinal microglia from enucleated eyes and compares their transcriptional profile with the one of whole retinal tissue, human brain microglia as well as classical, intermediate and non-classical monocytes. Finally, human retinal microglia are compared to murine retinal microglia, isolated from Cx3cr1GFP/+ mice. Whereas human retinal microglia exhibited a high grade of similarity in comparison to their counterparts in the brain, several enriched genes were identified in retinal microglia when compared to whole retinal tissue, as well as classical, intermediate, and non-classical monocytes. In relation to whole retina sequencing, several risk genes associated with age-related macular degeneration (AMD) and diabetic retinopathy (DR) were preferentially expressed in retinal microglia, indicating their potential pathophysiological involvement. Although a high degree of similarity was observed between human and murine retinal microglia, several species-specific genes were identified, which should be kept in mind when employing mouse models to investigate retinal microglia biology. In summary, this study provides detailed insights into the molecular profile of human retinal microglia, identifies several tissue-specific and species-specific genes in comparison to human brain microglia and murine retinal microglia, and thus highlights the significance of retinal microglia in human retinal diseases and for translational research approaches.